2018
DOI: 10.22456/1679-9216.14953
|View full text |Cite
|
Sign up to set email alerts
|

Biofilmes formados em matéria-prima em contato com leite: fatores de virulência envolvidos

Abstract: Biofilmes bacterianos representam uma preocupação à indústria de alimentos por sua potencialidade em resistir a tratamentos antimicrobianos, além de degradar e contaminar os alimentos com patógenos. O presente trabalho avaliou a relação entre fatores de adesão e hidrofobicidade celular na formação de biofilmes, bem como as atividades citotóxica e proteolítica de isolados bacterianos do biofilme. Corpos de prova compostos de polipropileno, aço inoxidável e pano de algodão foram imersos em leite in natura, em di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…It was observed that although there was no growth of the S. aureus colonies after 24 hr at 25 °C, there was a growth of both species at this temperature after 48 hr. This demonstrates the superior ability of the Gram‐negative bacteria to adhere and adapt to surfaces in comparison with the Gram‐positive bacteria as previously reported by Flach et al (). This suggests that after the adhesion and growth of E. coli on the surface, S. aureus may have adhered to the EPS already formed by E. coli .…”
Section: Resultssupporting
confidence: 83%
“…It was observed that although there was no growth of the S. aureus colonies after 24 hr at 25 °C, there was a growth of both species at this temperature after 48 hr. This demonstrates the superior ability of the Gram‐negative bacteria to adhere and adapt to surfaces in comparison with the Gram‐positive bacteria as previously reported by Flach et al (). This suggests that after the adhesion and growth of E. coli on the surface, S. aureus may have adhered to the EPS already formed by E. coli .…”
Section: Resultssupporting
confidence: 83%
“…The ability of S. aureus isolates from milk to form biofilms has also been demonstrated. Fox, Zadoks, and Gaskins (2005) Factors related to physicochemical properties of the surface material, temperature, pH, and expression of virulence factors (Flach, Karnopp, & Corção, 2005) influence the attachment of macromolecules and, as a result, biofilm formation.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Biofilms manifest unique developmental properties and phenotypic traits that favor protection from the external environment and provide better adhesion to surfaces. Thus, they reduce susceptibility to commercialized antimicrobials, becoming more resistant in environments with adverse conditions (Flach et al, 2005;Pasternak, 2009). The presence of biofilms causes surface deterioration and/or proliferation of pathogenic microorganisms, leading to damage in industry when present on equipment, and in health by increasing the mortality rate due to diseases caused by the resistance of bacteria to antimicrobials and disinfectants.…”
Section: Introductionmentioning
confidence: 99%